Pengaruh Lingkungan Kerja Fisik dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT Mayora Indah Tbk Cabang Bogor - Luthfia, Annisa; S.T.,MPd, Dr. Thamrin (Yayasan Sahabat Cendekia Jaya, 2025)
The purpose of this study was to determine the effect of physical work environment and work discipline on employee performance at PT Mayora Indah Tbk Bogor Branch, both partially and simultaneously. The method used is a quantitative method with an associative approach. The sampling technique used is saturated sampling and a sample of 65 respondents was obtained from the entire population. Data processing uses SPSS software version 27 which includes validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of the study indicate that the physical work environment has a significant effect on employee performance as indicated by the t-count value> t-table, namely (9.714> 1.9983), a significance value of (0.0000 <0.05), and a determination coefficient value of 60%. Work discipline has a significant effect on employee performance as shown by the t-count value > t-table, namely (12.201 > 1.9983), a significance value of (0.0000 < 0.05), and a determination coefficient of 70.3%. The physical work environment and work discipline simultaneously have a significant effect on employee performance as shown in the regression equation Y = 4.345 + 0.362X1 + 0.642X2, the f-count value > f-table (80.055 > 3.145), a significance value of (0.0000 < 0.05), and a determination coefficient value of 72.1% while the remaining 27.9% is influenced by other factors outside the study.